2011
DOI: 10.1128/cvi.00352-10
|View full text |Cite
|
Sign up to set email alerts
|

Increased Pulmonary Tumor Necrosis Factor Alpha, Interleukin-6 (IL-6), and IL-17A Responses Compensate for Decreased Gamma Interferon Production in Anti-IL-12 Autovaccine-Treated,Mycobacterium bovisBCG-Vaccinated Mice

Abstract: Interleukin-12 (IL-12Purified protein derivative-induced tumor necrosis factor alpha (TNF-␣), IL-6, and IL-17A levels, however, were highest in lungs from BCG-vaccinated/IL-12-neutralized animals, and even unstimulated lung cells from these mice produced significant levels of the three cytokines. Mycobacterium-specific IL-4 and IL-5 production levels were overall very low, but IL-12 neutralization resulted in increased concanavalin A-triggered polyclonal secretion of these Th2-type cytokines. These results sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…More recently, IL‐23 was shown to be required for long‐term control of M. tuberculosis , and moreover, the IL‐23/IL‐17A axis is important in vaccine‐induced protection by promoting an optimal IFN‐γ recall response in the lungs . Finally, we have shown that BCG‐induced protection against M. tuberculosis in mice treated with an auto‐vaccine against IL‐12p70 (which specifically neutralized IL‐12 while leaving the IL‐23 axis intact) was only marginally affected by the IL‐12 neutralization and that the concomitant decreased IFN‐γ response could be compensated by increased production of TNF‐α, IL‐6 and IL‐17A . However, strong IL‐17A responses do not necessarily correlate with strong protection, as boosting BCG vaccinated mice with MVA85A did not increase the protective efficacy of the BCG vaccine against M. tuberculosis in long‐term survival experiments, despite a dramatically increased IL‐17A and IFN‐γ response .…”
Section: Introductionmentioning
confidence: 77%
“…More recently, IL‐23 was shown to be required for long‐term control of M. tuberculosis , and moreover, the IL‐23/IL‐17A axis is important in vaccine‐induced protection by promoting an optimal IFN‐γ recall response in the lungs . Finally, we have shown that BCG‐induced protection against M. tuberculosis in mice treated with an auto‐vaccine against IL‐12p70 (which specifically neutralized IL‐12 while leaving the IL‐23 axis intact) was only marginally affected by the IL‐12 neutralization and that the concomitant decreased IFN‐γ response could be compensated by increased production of TNF‐α, IL‐6 and IL‐17A . However, strong IL‐17A responses do not necessarily correlate with strong protection, as boosting BCG vaccinated mice with MVA85A did not increase the protective efficacy of the BCG vaccine against M. tuberculosis in long‐term survival experiments, despite a dramatically increased IL‐17A and IFN‐γ response .…”
Section: Introductionmentioning
confidence: 77%
“…There is substantial evidence that both pro‐ and anti‐inflammatory elements are present in the immune response to Mtb infection, and that both play essential roles . A pro‐inflammatory TH1 response driven by CD4+ T cells producing IL‐2, IFN‐γ, and TNF is essential for controlling Mtb infection . CD4+ and CD8+ T cells produce cytokines that activate other immune cells, including activation of macrophages that can kill Mtb, and cytotoxic CD8+ T cells that can kill Mtb‐infected macrophages .…”
Section: Experimental Support For a Balanced Response In Tbmentioning
confidence: 99%
“…21 A pro-inflammatory TH1 response driven by CD4+ T cells producing IL-2, IFNγ, and TNF is essential for controlling Mtb infection. [22][23][24][25][26][27] CD4+ and CD8+ T cells produce cytokines that activate other immune cells, including activation of macrophages that can kill Mtb, 1,28 and cytotoxic CD8+ T cells that can kill Mtb-infected macrophages. [29][30][31] Most Mtb-infected people, including people with active TB, have Mtb-specific TH1 responses suggesting TH1 responses are necessary, but not sufficient, factors in infection control.…”
Section: E Xperimental Supp Ort For a Bal An Ced Re S P On S E In Tbmentioning
confidence: 99%
“…25 Freches et al found that there is a significant elevation of IL-6 and TNF-α in the spleen and lungs after BCG immunization. 26 IL-6 induces naïve Th0 cell polarization to Th17 by activating the signal transducers and transcription activators 3 signalling pathway and then transcriptional activation of RORγt. 27 In the present study,…”
Section: Discussionmentioning
confidence: 99%